Predictors of Endothelial Cell Loss after Phacoemulsification for the Treatment of Primary Angle Closure - Carlo Alberto Cutolo; Chiara Bonzano; Carlo Catti; Alessandro Bagnis; Riccardo Scotto; Letizia Negri; Sara Olivari; Francesca Cappelli; Carlo Enrico Traverso (Journal of Ophthalmology)
Purpose. To investigate demographic and anatomical factors associated with a reduction in endothelial cell density (ECD) after phacoemulsification (PE) for the treatment of primary angle closure (PAC). Methods. In this prospective case series, ECD was evaluated by noncontact specular microscopy and biometric parameters by both noncontact optical biometry and anterior segment optical coherence tomography, preoperatively and at 12 months after surgery. Anterior segment biomicroscopy and gonioscopy were also performed. The change in ECD and its relation to clinical characteristics and biometric parameters were evaluated by linear regression analysis. Results. 44 patients with PAC were included in the study. The mean (SD) patient age was 71.6 (10.2) years; thirty-one (70.5%) of them were women. Coexistence of exfoliation syndrome (XS) was observed in 4 cases (9.1%). The mean (SD) ECD (cells/mm2) changed from 2275 (463) preoperatively to 1964 (613) postoperatively with a mean reduction of −310 (95% CI −445 to −176; p<0.001). In the multivariate regression model, after correction for age and lens status, XS was the only parameter associated with ECD percentage change (B = −36.00; p=0.001). Conclusion. PE in angle closure causes a significant ECD reduction. In our population of PAC patients, XS is significantly associated with ECD change. In this group of patients, a careful preoperative endothelial evaluation should be performed.